Implementasi Profil Pelajar Pancasila Melalui Pembiasaan Jum’at Berbagi Pada Siswa Kelas 1 C di MIN 3 Kebumen - Nur Khotijah; Atim Rinawati (IAINU Kebumen, 2023)
This study aims to describe the Pancasila Student Profiles Implementation Through Friday Sharing Habits for Class 1 C Students in Min 3 Kebumen. This study uses a particular qualitative research methodology. Researchers collected data using observation techniques, interviews, and documentation. Data analysis techniques are used: data reduction, data presentation, and conclusions. The study's findings show the Pancasila student profiles implemented in class 1 C MIN 3 Kebumen through sharing Fridays. And it needs to be improved to implement the Pancasila student profile as effectively as possible.